The Palgrave Handbook of Multidisciplinary Perspectives on Entrepreneurship (Springer International Publishing, 2018)
Departing from the traditional approach of surveying current and future trends and developments, this unique Handbook brings phenomena, theories, and concepts from multiple disciplines together to advance entrepreneurship. With original contributions from authors who are experts in their fields, the collection offers state-of-the-art insights into generating new areas for research, new theories and concepts, and new questions for policy debates - all aimed at advancing entrepreneurship. Divided into four sections and covering perspectives such as neuroscience, theology, organisational behavior and education, The Palgrave Handbook of Multidisciplinary Perspectives on Entrepreneurship is a rich source of information for researchers, educators, entrepreneurs, leaders and managers.